Semi-quantitative analysis on sea buckthorn phenolic-rich extract coating bone-like open porous NiTi-based alloy - Yuca, Hafize; Senocak, Taha Cagri; Yigit, Oktay; Albayrak, Muhammet Gokhan; Guvenalp, Zuhal (Cell Press, 2024)
This study investigates the feasibility of coating Ni-Ti alloy with sea buckthorn extract via a hydrothermal method for targeted delivery of beneficial phenolic compounds to bone tissue. The qualitative analysis confirmed the presence of flavonoids and tannins in sea buckthorn extract, supporting its osteogenic potential. The microhardness of the NiTi alloy substrate was suitable for biomedical applications, and successful coating was achieved without compromising its properties. NiTi alloy samples were coated with 18.1, 20.1, and 12.4 mg of extract, respectively. Comprehensive evaluations confirmed the successful integration of the extract onto the alloy's surface. The coated system exhibited sustained release properties over five days, with the highest release occurring on the first day (on average 32.1 % for the first peak and 72.1 % for the second peak), as determined by HPLC analysis. The findings demonstrate the potential of this novel approach in developing dual-functionality implants for bone health promotion. Overall, this study underscores the promising potential of Ni-Ti alloy coated with sea buckthorn extract as a targeted drug delivery system for bone tissue.
Keywords: Sea buckthorn; Nickel titanium-based alloy; Bone implant; Phenolics; HPLC